The types of hackers and cyberattacks in the aviation industry - Florido Benítez, Lázaro (My University, 2024)
The main goal of this study is to analyse the types of hackers and cyberattacks in the aviation industry, to enhance cybersecurity in the air sector. This manuscript has identified 12 different typologies of hackers in the aviation context. First, those hackers who exercise responsibility in proper, effective, ethical, and good practices to improve the safety of citizens and organizations, such as white unicorns, red, blue, green, and nation sponsored hackers. And second, those hackers that are devel- oping and using cyberattacks with bad practices to provoke serious material damage to public and private organizations, consumers, or even terrorist acts to kill people, including black, nation-state, cyberterrorist, whistle-blower, hacktivist, script kiddie, and gray hackers. Furthermore, findings reveal 54 cyberattacks documented in the period analysed (2000 – January 2024). Of the total cyberattacks in the period ana- lysed, 35 were perpetrated at airports (65%) and 19 by airlines (35%). This study also suggests some lines of action to ensure and guarantee the security of data and private information for business-to-consumer (B2C) and business-to-business (B2B) and their transactions in the aviation industry.
Keywords: Aviación - Industria; Líneas aéreas; Aeropuertos; Seguridad informática; Ciberterrorismo; Piratas informáticos; Typology; Motivations